Impacts of climate change on rice production in Africa and causes of simulated yield changes - Zwart, S.J. (2020)
This study is the first of its kind to quantify possible effects of climate change onrice production in Africa. We simulated impacts on rice in irrigated systems (dry sea-son and wet season) and rainfed systems (upland and lowland). We simulated theuse of rice varieties with a higher temperature sum as adaptation option. We simu-lated rice yields for 4 RCP climate change scenarios and identified causes of yielddeclines.